1955
DOI: 10.1002/cber.19550880506
|View full text |Cite
|
Sign up to set email alerts
|

Synthese des Guajacylglycerin‐β‐coniferyläthers und weitere Versuche im Zusammenhang mit dem Lignin

Abstract: ober die Synthese dea voranstohend geachilderten neuen Zwischenpduktas der Ligninbildung, dea G u a j a c y~l y c e r i n -8 -c~t h e r s ( I ) *), wird berichtat sowie uber andere Versuche, die damit im Zusammenhang stehen.In der vorhergehenden Arbeitl) wird die Isolierung einea neuen Zwischenproduktm der biochemischen Ligninsynthese beschrieben. Es handelt sich um den Guajacylglycerin-@-coniferyliither. Obwohl die Formulierung I die wahrscheinlichere war, konnte doch zuniichst nicht festgestellt werden, ob d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1955
1955
1986
1986

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…addition, syrupy cc-guaiacylglycerol action with the 04-position of another molecule and with OH) was isolated by countercurrent distribution 219 and characterised by conversion into the 2 : 4-dinitrophenyl ether of its dihydroderivative and by synthesis. 220 Freudenberg has suggested that these are intermediates (" sekundare Bausteine ") in lignin formation. However, none of the three dimeric products isolated has retained the reactive P-hydroxystyrene system and so they may be by-products rather than intermediates in DHP formation.…”
Section: Degradation Methodsmentioning
confidence: 99%
“…addition, syrupy cc-guaiacylglycerol action with the 04-position of another molecule and with OH) was isolated by countercurrent distribution 219 and characterised by conversion into the 2 : 4-dinitrophenyl ether of its dihydroderivative and by synthesis. 220 Freudenberg has suggested that these are intermediates (" sekundare Bausteine ") in lignin formation. However, none of the three dimeric products isolated has retained the reactive P-hydroxystyrene system and so they may be by-products rather than intermediates in DHP formation.…”
Section: Degradation Methodsmentioning
confidence: 99%
“…L'importance de ce mode de liaison (ß-0-4) fait de ce type de dimäres un modele privilegie pour aborder les 6tudes du biopolymere. Cette mothode initialement docrite par Adler et al (1952; a ensuite reprise par un bon nombre d'auteurs (Freudenberg et Eisenhut 1955;Kratzl et al 1959;Nimz 1967;Miksche 1973;Landucci etal. Bien qu'elle soit moins directe que les autres, eile presente en effet l'interet de donner acces ä des intermediaires qui sont des temoins potentiels pour l'analyse des melanges toujours complexes resultant des degradations chimiques ou microbiologiques des lignines ou des modeles eux-memes.…”
Section: Introductionunclassified